Dynamics in Physical Functioning Limitations - Neha Agarwal; Hans-Peter Kohler; Subha Mani (Institute of Labor Economics (IZA), 2017)
The extent to which physical functioning limitations result in permanent job loss, lowered lifetime income and assets, in part, depends upon the extent to which onset of these limitations becomes permanent. This paper uses five rounds of data from Malawi to examine path dependence in physical functioning limitations. We do so using a dynamic linear panel data model where the coefficient on the one-period lagged health outcome captures path dependence in functional limitations. Our preferred estimates indicate – (a) partial recovery from onset of functional limitations for males, (b) there is less recovery in severe limitations than moderate limitations for males, (c) perfect recovery from both moderate and severe functional limitation for females.
Keywords: J14; I15; I10; 330; activity of daily living; functional limitation; panel data; Malawi